2020
DOI: 10.1186/s12889-020-09794-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms and associated factors among patients with tuberculosis attending public health institutions in Gede’o zone, South Ethiopia

Abstract: Background Depression is a common mental disorder among patients with tuberculosis and it is associated with a greater risk of suicide, multidrug-resistant tuberculosis, and poor quality of life. Evidence suggests the early identification of depression among patients with tuberculosis is important to decrease adverse outcomes. However, there are limited studies that examined the prevalence and determinants of depressive symptoms among patients with tuberculosis. This study aimed to assess the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In our research, we discovered that 50% of patients with TB were depressed. The findings were similar to those of a cross-sectional study conducted by Dasa et al in Eastern Ethiopia and a study undertaken by Dahiya et al in Haryana, India [ 8 , 9 ]. It's also similar to other research done in Sub-Saharan Africa: Angola has 49.4% and the Southwest Region of Cameroon has a 61.1% prevalence of depression in patients with TB [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our research, we discovered that 50% of patients with TB were depressed. The findings were similar to those of a cross-sectional study conducted by Dasa et al in Eastern Ethiopia and a study undertaken by Dahiya et al in Haryana, India [ 8 , 9 ]. It's also similar to other research done in Sub-Saharan Africa: Angola has 49.4% and the Southwest Region of Cameroon has a 61.1% prevalence of depression in patients with TB [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…Being married does not offer any protection or benefits to patients with TB and depression. On the other hand, other research have revealed that depression in TB patients may be influenced by old age, substantial pathology, being single, and a lack of social support [ 9 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are different from studies conducted by previous researchers who said that older patients had greater depressive symptoms than younger people. 38 , 39 This difference is since adolescence is a period that susceptible to tuberculosis. 40 Adolescence is a developmental age characterized by biological and social changes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, higher levels of PF in childhood, particularly cardiorespiratory fitness, muscle strength, and motor skills, have been associated with a healthier cardiovascular profile later in life ( 56 ). Optimal PF levels may mitigate metabolic breakdown associated with excess fat ( 11 ) and have positive effects on mental and skeletal health ( 12 ). For these reasons, the assessment of PF in children provides relevant clinical and public health information that can be used to maintain and improve children's health ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Muscular strength and endurance are associated with improved quality of life and the ability to perform functional tasks without exhaustion. Maintaining muscle, bone, and joint strength allows for better movement and reduces the risk of osteoporosis and falls in the elderly ( 12 ). Flexibility is also a factor that affects the ability of individuals to vigorously carry out their daily activities.…”
Section: Introductionmentioning
confidence: 99%